BRAIN ENERGY METABOLISM AND MITOCHONDRIAL DYSFUNCTION IN ACUTE AND CHRONIC HEPATIC ENCEPHALOPATHY - Rama Rao, Kakulavarapu V. (Neurochem Int, 2011)
One proposed mechanism for acute and chronic hepatic encephalopathy (HE) is a disturbance in cerebral energy metabolism. This article reviews the current status of this mechanism in both acute and chronic HE, as well as in other hyperammonemic disorders. This article reviews abnormalities in glycolysis, lactate metabolism, citric acid cycle, and oxidative phosphorylation and associated energy impairment. Additionally, the role of mitochondrial permeability transition (mPT), a recently established factor in the pathogenesis of HE and hyperammonemia, is emphasized. Energy failure appears to be an important pathogenetic component of both acute and chronic HE and a potential target for therapy.